Standar Isi Kurikulum Muatan Lokal Jenjang SD di Kabupaten Ogan Komering Ulu Timur ditinjau dari Perspektif Enkulturasi Budaya - Syidik, Syahrul; Karsono, Karsono (Universitas Sebelas Maret, 2025)
This study examines the profile of the local content curriculum in elementary schools in Ogan Komering Ulu Timur (OKUT) Regency from the perspective of cultural enculturation. It evaluates curriculum elements content standarts, focusing on how Komering cultural values are integrated into primary education. Using a qualitative methodology and a literature study approach, data were gathered from three schools representing OKUT’s diverse cultural populations through observations, interviews, and document analysis. This study applies Miles and Huberman's interactive model and the encluturation dimension analysis framework to seven aspects of universal culture to analyze cultural values such as language, local knowledge, social organization, tools and technology, economy, religion, and art, which are contained in the content standards. Findings indicate that while language, local knowledge, social organization, religion and arts are well integrated. Economic and technological aspects remain underrepresented in current research and data analysis. The research highlights the need for a more inclusive content curriculum to promote cultural literacy and recommends further studies on cultural integration in education systems.